Lars von Trier's renewal of film 1984-2014 : signal, pixel, diagram - Thomsen, Bodil Marie, 1956- (Aarhus University Press, 2018)
Danish director Lars von Trier has produced more than 20 films since his first appearance with 'The Elements of Crime' in 1984. One of the most acknowledged - and most controversial - film directors of our time, Trier's films often escape the representational production of meaning. In 'Lars von Trier's Renewal of Film 1984-2014. Signal, Pixel, Diagram' scholar Bodil Marie Stavning Thomsen offers a comprehensive discussion of Lars von Trier's collected works. Examining Trier's experiments with narrative forms, genre, camera usage, light, and colour tones, she shows how Trier's unique ethically involving style activates the viewer's entire perception apparatus. In understanding this affective involvement, the author frames the discussion around concepts from Gilles Deleuze, Alois Riegl, Brian Massumi and others on the haptic image, the diagram, affect and the signaletic material.